2018
DOI: 10.1016/j.scitotenv.2017.09.235
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning multi-source uncertainties in simulating nitrogen loading in stream water using a coherent, stochastic framework: Application to a rice agricultural watershed in subtropical China

Abstract: Uncertainty is recognized as a critical consideration for accurately predicting stream water nitrogen (N) loading, but identifying the relative contribution of individual uncertainty sources within the total uncertainty remains unclear. In this study, a powerful method, referred to as the Bayesian inference combined with analysis of variance (BayeANOVA) was adopted to detect the timing and magnitude of multiple uncertainty sources and their relative contributions to total uncertainty in simulating daily loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…We use analysis of variance (ANOVA) to partition the variability in simulated flood peak frequency into various contributors, which are shown in Table . ANOVA is useful for estimating the variation of response due to different factors (Bosshard et al, ; Ma et al, ) including continuous, discrete, and mixed variables (Cardinal & Aitken, ; Yip et al, ). Yip et al () use ANOVA to partition sources of variability in global climate model simulations, while Meresa and Romanowicz () and Bosshard et al () apply it to hydrologic extremes.…”
Section: Methodsmentioning
confidence: 99%
“…We use analysis of variance (ANOVA) to partition the variability in simulated flood peak frequency into various contributors, which are shown in Table . ANOVA is useful for estimating the variation of response due to different factors (Bosshard et al, ; Ma et al, ) including continuous, discrete, and mixed variables (Cardinal & Aitken, ; Yip et al, ). Yip et al () use ANOVA to partition sources of variability in global climate model simulations, while Meresa and Romanowicz () and Bosshard et al () apply it to hydrologic extremes.…”
Section: Methodsmentioning
confidence: 99%
“…For example, van Griensven et al [42] found that the influence of input uncertainty (i.e., climate and pollution data) is minor in comparison to SWAT parameterization uncertainty. Similarly, Ma et al [43] found that parameters uncertainty is the most significant factor in uncertainty analysis in comparison with precipitation input uncertainty. Our results indicate that the uncertainty in management setup a minor role in the overall uncertainty.…”
Section: Uncertainty Analysismentioning
confidence: 94%
“…Analysis of variance (ANOVA) is useful for estimating the variation of response due to different factors (Bosshard et al, 2013;Ma et al, 2018) including continuous, discrete, and mixed variables (Cardinal & Aitken, 2013). Yip et al (2011) used ANOVA to partition sources of variability in global climate model simulations, while (Meresa & Romanowicz, 2017) apply it to hydrologic extremes.…”
Section: The Contribution Of Rainfall Spatial and Temporal Heterogene...mentioning
confidence: 99%